Bushmeat hunting and extinction risk to the world’s mammals - Ripple, William J.; Abernethy, Katharine; Betts, Matthew G.; Chapron, Guillaume; Dirzo, Rodolfo; Galetti, Mauro [UNESP]; Levi, Taal; Lindsey, Peter A.; Macdonald, David W.; Machovina, Brian; Newsome, Thomas M.; Peres, Carlos A.; et al. (The Royal Society, 2016)
Terrestrial mammals are experiencing a massive collapse in their population sizes and geographical ranges around the world, but many of the drivers, patterns and consequences of this decline remain poorly understood. Here we provide an analysis showing that bushmeat hunting for mostly food and medicinal products is driving a global crisis whereby 301 terrestrial mammal species are threatened with extinction. Nearly all of these threatened species occur in developing countries where major coexisting threats include deforestation, agricultural expansion, human encroachment and competition with livestock. The unrelenting decline of mammals suggests many vital ecological and socio-economic services that these species provide will be lost, potentially changing ecosystems irrevocably. We discuss options and current obstacles to achieving effective conservation, alongside consequences of failure to stem such anthropogenic mammalian extirpation. We propose a multipronged conservation strategy to help save threatened mammals from immediate extinction and avoid a collapse of food security for hundreds of millions of people.
Keywords: Bushmeat; Extinction; Hunting; Mammals; Wild meat